Media Permainan Teka-Teki Silang Untuk Pembelajaran Bahasa Inggris Siswa Tunarungu - Arofah, Sufi Jamilatu Nur; Efendi, Mohammad (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2015)
Learning English for children with hearing impairment is not a simple thing. Children with hearing impairment have problems in terms of the language, poor of vocabulary. This research was aimed at developing a crossword puzzle game as a medium of learning English for 7th grade of hearing impairment children. This research used a model of research and development. The product of this development was a crossword puzzle game that is used as a medium of teaching and learning English grade VII of hearing impairment. The products tested to the media expert, material expert and students. The results of the trial showed that the crossword puzzle games in generally was feasible to be used in English learning. Revision was focused on clarity of instruction.Pembelajaran bahasa Inggris untuk siswa tunarungu bukanlah suatu hal yang sederhana, dikarenakan keterbatasan kemampuan menyimak. Penelitian ini bertujuan untuk mengembangkan permainan teka-teki silang sebagai media pembelajaran bahasa Inggris untuk kelas VII tunarungu. Berdasarkan uji coba produk terpadu kepada ahli media, ahli materi dan siswa, dapat disimpulkan bahwa permainan teka-teki silang secara umum layak digunakan dalam pembelajaran bahasa Inggris. Revisi berfokus pada kejelasan instruksi.